2001
DOI: 10.1007/s100670170063
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Sacroiliitis in Behçet’s Disease

Abstract: The aim of the study was to evaluate the prevalence of sacroiliitis in a group of patients with Behçet's disease (BD). Pelvic X-rays of 27 patients with BD responding to the International Study Group of BD and 30 controls (15 AS and 15 sciatica) were read blind and sacroiliac involvement was graded according to the New York criteria. In a second step, patients or controls with equivocal sacroiliitis had a sacroiliac CT scan. Two patients with BD (7.4%) and all patients with AS had evident bilateral sacroiliiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 5 publications
5
14
0
3
Order By: Relevance
“…5-97% clinically based arthritis in BD was previously reported [3,20,[24][25][26]. In our study 12/25 (48%) had clinically evident arthritis and this concurs with the incidence (about 50%) in the Mediterranean (Turkey, Egypt and Lebanon), and North Africans (Tunisia and Morocco) [23,[26][27][28], however in Asia (Oman) [29] or far Asians (Korea) [24,26], this incidence shoots up to 75-97%. 2/25 (8%) of our cases had rheumatoid-like hand findings in the form of swelling of PIPs and MCPs.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…5-97% clinically based arthritis in BD was previously reported [3,20,[24][25][26]. In our study 12/25 (48%) had clinically evident arthritis and this concurs with the incidence (about 50%) in the Mediterranean (Turkey, Egypt and Lebanon), and North Africans (Tunisia and Morocco) [23,[26][27][28], however in Asia (Oman) [29] or far Asians (Korea) [24,26], this incidence shoots up to 75-97%. 2/25 (8%) of our cases had rheumatoid-like hand findings in the form of swelling of PIPs and MCPs.…”
Section: Discussionsupporting
confidence: 77%
“…Skin lesions and positive SPT were found in 24% & 16% respectively compared to 16% in a North African study [23], others reported higher positive SPT (51% & 61.4%) [20,30]. These differences are attributable to geographic, environmental and genetic factors variability [21].…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…En s›k, diz ve dirsek gibi orta büyüklükteki eklemler etkilenir. Olgular›n % 6-38'inde sakroiliit görülür (5,6). Literatürde Behçet hastal›¤› ve subklavyen arter t›kan›k-l›¤› birlikteli¤ini bildiren bir olgu vard›r (7).…”
Section: Tart›flmaunclassified
“…Aunque sea más frecuente la forma oligoarticular que la sacroiliaca, el hallazgo de sacroileitis en la EB hace que sea necesario realizar un diagnóstico diferencial con las espondiloartropatías seronegativas (7). Otro punto importante a destacar, a propósito de nuestro caso, es la necesidad de utilizar técnicas de imagen apropiadas, ya que en grados leves-moderados en donde la exploración y la radiografía simple pueden ser normales, es necesario la utilización de la TC o la RMN para el diagnóstico (8)(9)(10) gún internista podría estar en desacuerdo. No obstante, creo que quizá enfoca el tema de un modo demasiado tradicional y un tanto restrictivo.…”
unclassified